2013
DOI: 10.1161/atvbaha.112.300840
|View full text |Cite
|
Sign up to set email alerts
|

Notch-Dependent Regulation of the Ischemic Vasodilatory Response—Brief Report

Abstract: Objective-We have recently described that Notch activates nitric oxide (NO) signaling in the embryonic endocardium. Both Notch signaling and NO signaling have been shown to be important during adult arteriogenesis. Notch has been shown to be required for remodeling of the collateral vessels, whereas NO is required for the initial vasodilatory response to ischemia. Whether Notch also has an impact on the vasodilatory phase of arteriogenesis after ischemia is not known. We tested the hypothesis that endothelial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 12 publications
2
13
0
Order By: Relevance
“…9). dnMAML has been used to assess the effect of pan-inhibition of Notch signaling used in various vascular models, and although found to be specifically inhibitory to Notch signaling (22)(23)(24)(25)(26), one cannot entirely rule out the possibility that some unknown pathway is also impacted. We hypothesized that increasing VEGFA signaling would sensitize tumors to Notch inhibition, as VEGFA activates endothelial cell Notch signaling by increasing Dll4 expression in tip cells (12)(13)(14)27).…”
Section: Resultsmentioning
confidence: 99%
“…9). dnMAML has been used to assess the effect of pan-inhibition of Notch signaling used in various vascular models, and although found to be specifically inhibitory to Notch signaling (22)(23)(24)(25)(26), one cannot entirely rule out the possibility that some unknown pathway is also impacted. We hypothesized that increasing VEGFA signaling would sensitize tumors to Notch inhibition, as VEGFA activates endothelial cell Notch signaling by increasing Dll4 expression in tip cells (12)(13)(14)27).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, loss of blood flow led to increased vascular Notch signalling in the vasculature of zebrafish embryos63. Notch facilitates vessel constriction during the regression (pruning) of capillaries64, but Notch activity is also required for nitric oxide induction and vasodilation in response to ischaemia in the adult vasculature65. Furthermore, Notch activation is a hallmark of arteriovenous malformations and constitutive activation of Notch4 has been shown to induce the enlargement of capillary vessels into arteriovenous shunts66.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated a direct link between Notch signaling and eNOS activity. 18, 19 Notch activation activates eNOS, which induces NO synthesis. In an animal model of hindlimb ischemia, Notch inhibition in endothelial cells reduced reperfusion and NO generation.…”
Section: Discussionmentioning
confidence: 99%
“…In an animal model of hindlimb ischemia, Notch inhibition in endothelial cells reduced reperfusion and NO generation. 18 Ang1 is an angiogenic factor that also activates the pro-survival signaling pathway and initiates stem cell homing in the setting of myocardial ischemia. 20 In a porcine model of myocardial infarction, co-expression of VEGF and Ang1 was shown to increase angiogenesis, myocardial perfusion, and cardiomyocyte proliferation in ischemic myocardium.…”
Section: Discussionmentioning
confidence: 99%